The Influence of Knowledge Management on the Culture of Knowledge Sharing With Leadership as an Intervening Variable at the Ministry of Religion of Binjai City - Kartika Ujiani Nasution; Abdi Sugiarto (International Journal of Society and Law, 2024)
Knowledge management in government institutions is essential to improve operational efficiency, innovation, and quality of public services, as well as ensure adaptability, transparency, accountability, and responsiveness to the needs of society in the era of globalization and increasingly fierce competition. The purpose of this study is to find out and analyze the influence of Knowledge Management on the Culture of Knowledge Sharing mediated by the Leadership at the Office of the Ministry of Religion of Binjai City. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 105 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that Knowledge Management has a positive and significant influence on Knowledge Sharing Culture, with T-statistical values of 2.973 > 1.96 and P-Values of 0.003 < 0.05, which means that an increase in Knowledge Management will significantly improve the Knowledge Sharing Culture. In addition, Knowledge Management also has a positive and significant effect on Leadership, shown by a T-statistical value of 78.253 > 1.96 and a P-Value of 0.000 < 0.05, indicating that improving Knowledge Management will significantly improve organizational leadership. Other findings showed that Leadership had a positive and significant effect on the Knowledge Sharing Culture, with a T-statistic value of 5.668 > 1.96 and a P-Value of 0.000 < 0.05, which indicates that an increase in Leadership will significantly improve the Knowledge Sharing Culture. Indirect influence analysis showed that Leadership was able to intervene in the influence between Knowledge Management and Knowledge Sharing Culture, with a T-statistical value of 5.796 > 1.96 and a P-Value of 0.000 < 0.05. These results provide important insights that Leadership plays a significant intermediary variable in the relationship between Knowledge Management and Knowledge Sharing Culture at the Office of the Ministry of Religion of Binjai City. These findings underscore the importance of integrating knowledge management strategies and leadership development to improve the culture of knowledge sharing in government institutions.